2016
DOI: 10.4040/jkan.2016.46.5.710
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Self-efficacy Promoting Vestibular Rehabilitation Program for Patients with Vestibular Hypofunction

Abstract: This is an Open Access article distributed under the terms of the Creative Commons Attribution NoDerivs License. (http://creativecommons.org/licenses/by-nd/4.0) If the original work is properly cited and retained without any modification or reproduction, it can be used and re-distributed in any format and medium. Purpose: In this study an examination was done of the effect of self-efficacy promoting vestibular rehabilitation (S-VR) on dizziness, exercise selfefficacy, adherence to vestibular rehabilitation (VR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…A total of three studies reported self‐management results that were measured using the Hill‐Bone Compliance to High Blood Pressure Therapy Scale (Abu‐El‐Noor et al, 2021), Adherence to Treatment of Systemic Hypertension (Mattei da Silva et al, 2020), and the tool developed by Lee (1995). Nurse‐led DHIs were shown to improve self‐management in people with hypertension (SMD = 0.98, 95% CI: 0.58 to 1.37, Z = 4.39, p < 0.05, I 2 = 63.2%, Figure 5a).…”
Section: Resultsmentioning
confidence: 99%
“…A total of three studies reported self‐management results that were measured using the Hill‐Bone Compliance to High Blood Pressure Therapy Scale (Abu‐El‐Noor et al, 2021), Adherence to Treatment of Systemic Hypertension (Mattei da Silva et al, 2020), and the tool developed by Lee (1995). Nurse‐led DHIs were shown to improve self‐management in people with hypertension (SMD = 0.98, 95% CI: 0.58 to 1.37, Z = 4.39, p < 0.05, I 2 = 63.2%, Figure 5a).…”
Section: Resultsmentioning
confidence: 99%
“…The interest in applying visual stimuli to produce neural adaptation and improvement in functional abilities in this population has drawn interest from technology-assisted methods (Zanier et al, 2018). The use VPT, such as VR and AR, has been recently suggested as advantageous in other neurological groups (Lee & Choi-Kwon, 2016), though the effectiveness and efficacy of such an intervention is limited at present. Within the concussion population, more recent interest has focused on VR and AR's use in the assessment process (Wright et al, 2017), with a gap in the literature around its potential use in treatment.…”
Section: Explore Importance Of the Problemmentioning
confidence: 99%
“…After that, handouts are provided for patients to exercise at home (Kim, 2013;Lee et al, 2011). Recently, Lee and Choi-Kwon (2016) reported that the implementation rate of self-home exercise for patients with peripheral vestibular disease was very low. Many researchers reported that individualized VR tailored by a physical therapist was more effective than general VR (Gottshall, 2011;Norré and Beckers, 1988;Sessoms et al, 2015) because physical therapists play an important role in directly restoring patient function and return to daily life by identifying the patient's specific impairments and functional limitations.…”
mentioning
confidence: 99%